2023
DOI: 10.18326/ijims.v13i1.57-84
|View full text |Cite
|
Sign up to set email alerts
|

Multicultural Quality of Life: experiences of a South Australian Muslim community amid the COVID-19 pandemic

Abstract: Muslims have a strong sense of obligation in which Islam informs their ways of life. As a religious minority within Australia, these obligatory practices may not be well understood by mainstream policy, health, and welfare services. This mixed-method, cross-sectional study assessed the self-reported quality of life (QoL), worldviews, and subjective experiences of religiosity and/or cultural identity of adults from a Muslim community affiliated with the Adelaide Mosque, metropolitan South Australia. Data were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In terms of the aspirational dimensions, this community has shown the capacity to maintain hope in the face of the poor health, socio-emotional outcomes, and wellbeing often experienced by religious, cultural or racial others, as established in other research (Abood et al 2021;Chen et al 2022;Hamiduzzaman et al 2022;McLaren et al 2022;Monani 2018). Prior research on the quality of life of a South Australian Muslim community in the first year of the COVID-19 pandemic likewise showed aspirational capital (McLaren et al 2023;Patmisari et al 2022) and potential associations with community cultural wealth.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In terms of the aspirational dimensions, this community has shown the capacity to maintain hope in the face of the poor health, socio-emotional outcomes, and wellbeing often experienced by religious, cultural or racial others, as established in other research (Abood et al 2021;Chen et al 2022;Hamiduzzaman et al 2022;McLaren et al 2022;Monani 2018). Prior research on the quality of life of a South Australian Muslim community in the first year of the COVID-19 pandemic likewise showed aspirational capital (McLaren et al 2023;Patmisari et al 2022) and potential associations with community cultural wealth.…”
Section: Discussionmentioning
confidence: 75%
“…Indifference leads to marginality, and marginality leads to inequity in health and welfare knowledge, service access, and the availability of suitable support (Riggs et al 2015;Shahin et al 2021). When such barriers exist, the outcomes for members of Muslim and other minority groups may be low levels of health literacy (Hamiduzzaman et al 2022), poor socio-emotional health and wellbeing (Abood et al 2021;McLaren et al 2022), higher rates of family violence (Chen et al 2022), diminished quality of life (McLaren et al 2023;Patmisari et al 2022), and silencing (McLaren 2016;Nawaz and McLaren 2016). Researchers have shown that implementation science incorporating faith-based strategies has the potential to bridge the gaps and improve the outcomes, achieving harmony in non-Muslim communities (Abu Khait and Lazenby 2021; In our reflections, we draw on the idea of community cultural wealth, as originally conceptualised by Oliver and Shapiro (1995), emphasising the value of knowledge, practices, and relationships in shaping the outcomes for people in various socio-cultural or religious contexts.…”
Section: Introductionmentioning
confidence: 99%
“…The Prophet's birthday is considered important for Muslims because it is a concrete manifestation of love and respect for the Prophet Muhammad SAW. This celebration is a medium for expressing admiration, affection and loyalty to the Prophet as the main role model in life [5], [6]. Muslims in Iran and Pakistan, for example, are very vocal in celebrating the Prophet's birthday.…”
Section: Introductionmentioning
confidence: 99%